EFFICACY AND SAFETY OF PIDOTIMOD IN THE TREATMENT OF RECURRENT RESPIRATORY INFECTIONS IN CHILDREN - G. Caramia; E. Clemente; R. Solli; V. Mei; R. Cera; V. Carnelli; V. Venturoli; A. Corsini ("Paediatrician" Publishers LLC, 2008)
The immunomodulating activity of pidotimod (imunorix) was evaluated in a doublebblind, placebobcontrolled, randomized, multicentre trial, on 120 pediatric patients affected by recurrent respiratory infections. Antibiotic therapy and time of hospitalization were shorter in the patients taking pidotimod, and clinical recovery began more rapidly. A significant trend to normalization of the immune response, evidenced by chemotaxis and leukocyte phagocytosis index, was found only in patients treated with pidotimod. A significant decrease in the risk of relapses was observed in patients treated with pidotimod (35%), as well as a reduction of hospitalization (86%) and a decreased antibiotic therapy (47%). If a relapse occurred, the response of treated patients was quicker (fever, antibiotic therapy, hospitalization). No side effects, including significant alterations in main laboratory parameters were observed. The management of children with recurrent respiratory infections with pidotimod reduces the duration and severity of acute condition of infections and risk of relapse. pidotimod is well tolerated and maintains beneficial effect of treatment. Key words: children, pidotimod, recurrent respiratory infections, management.